A bio-based synthetic leather based on plant fibers and a method for preparing the same
Patent Information
- Application Number
- CN202611442621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-11-03
AI Technical Summary
With existing technologies, bio-based synthetic leather with high plant fiber content cannot simultaneously achieve both flexural strength under extreme low-temperature conditions and interfacial peel strength after hygrothermal aging, resulting in problems such as interfacial stress concentration and insufficient interfacial hydrolysis resistance.
The plant fiber system, designed with heterogeneous division of labor, uses polydopamine-coated bamboo fiber, lignin-retaining fir and pine fiber, and loaded porous corn cob, combined with two-stage temperature-controlled processing, to construct a gradient flexible transition layer and a dynamic borate ester crosslinking network, thereby achieving effective connection between the fiber and the matrix.
With a high plant fiber content, synthetic leather exhibits significantly improved folding life at extreme low temperatures, retains up to 90% of its peel strength after wet heat aging, and possesses excellent weather resistance and moderate levels of antibacterial and antifungal properties.
Smart Images

Figure CN123025555A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of synthetic leather technology, and in particular to a bio-based synthetic leather based on plant fibers and its preparation method. Background Technology
[0002] Synthetic leather is widely used in upholstered furniture, footwear, bags, and outdoor furniture. Traditional synthetic leather is based on petroleum-based polyvinyl chloride or polyurethane, which has a high carbon footprint and is non-renewable. With increasingly stringent environmental regulations and growing demand for sustainable materials in downstream markets, bio-based synthetic leather, with bio-based polyurethane as the matrix and plant fibers as the reinforcing filler, has become an important development direction for the industry. Furthermore, the market's requirements for its bio-based content are constantly increasing, with plant fiber filler content reaching 40% to 50% becoming a clear target for high-end products.
[0003] Existing plant fiber-filled synthetic leather technologies typically use a single type of wood flour, bamboo flour, or straw flour as filler. The fibers are first subjected to alkaline cooking and bleaching to remove lignin and improve color. Then, the fiber surface is modified by impregnation or spraying with a silane coupling agent hydrolysate. Finally, it is composited with polyurethane through coating or melt extrusion. This type of technology can generally meet conventional usage requirements when the plant fiber filler content is below 20%.
[0004] However, when the plant fiber filling content increases to 40% to 50%, the above-mentioned technologies present an irreconcilable contradiction. On the one hand, the silane coupling agent hydrolyzes and condenses on the fiber surface to form a dense and rigid silica cross-linked layer. The modulus of highly crystalline cellulose fibers is above 20 GPa, while the modulus of the polyurethane matrix is only tens of megapascals, resulting in a steep modulus step between the two. At the extreme low temperature of -20℃, the matrix chain segments freeze, and the mismatch in the thermal expansion coefficients of the fiber and the matrix further exacerbates the stress concentration at the interface. When repeatedly bent, microcracks rapidly initiate and propagate at the interface. In the low-temperature flexural endurance test conducted according to QB / T 2714-2005, cracks often appear after 15,000 to 45,000 bends. On the other hand, measures taken by the industry to improve low-temperature flexibility, such as adding plasticizers or increasing the proportion of soft segments, significantly weaken the interfacial hydrolysis resistance. The capillary channels of hydrophilic plant fibers become rapid pathways for moisture transport. Under humid heat conditions of 85℃ and 85%RH, the urethane bonds undergo hydrolysis, which is accelerated by the autocatalysis of the amines produced by hydrolysis. Plasticizer migration further erodes the interface, and the peel strength decreases significantly after 336 hours of aging, with a retention rate generally less than 50%. Thus, a mutually exclusive relationship is formed between low-temperature flexural strength and peel strength after humid heat aging.
[0005] Therefore, how to ensure that bio-based synthetic leather has both flexural strength under extreme low temperature conditions and interfacial peel strength after hygrothermal aging with a high plant fiber filling content of 40% to 50% is a core technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a bio-based synthetic leather based on plant fibers and its preparation method. This invention abandons the traditional approach of treating plant fibers as a uniform filler, instead employing a heterogeneous design for four plant-derived components: polydopamine-coated bamboo fiber serves as a rigid load-bearing skeleton; lignin-retaining fir and pine fibers act as dynamic cross-linking nodes and antioxidant functional carriers; and expanded-pore porous corn cobs serve as micro-reservoirs for interfacial release agents. Combined with a two-stage temperature-controlled processing method, the interfacial release agent seeps out from the pores of the corn cob during the thermoforming stage, constructing a gradient flexible transition layer in situ on the surface of the rigid fibers and forming a dynamic borate ester cross-linking network with lignin. This results in excellent low-temperature folding strength and peel strength after wet heat aging, even with a high plant fiber filler content.
[0007] According to one aspect of the present invention, a bio-based synthetic leather based on plant fibers is provided, comprising a synthetic leather base layer, wherein the raw materials for preparing the synthetic leather base layer include a bio-based polyurethane and a plant fiber system; the plant fiber system includes polydopamine-coated bamboo fiber, fir fiber, pine fiber, and a loaded porous corn cob; the polydopamine-coated bamboo fiber is bamboo fiber with a polydopamine layer coated on its surface; the fir fiber and the pine fiber are fibrous powders obtained by mechanically crushing fir and pine wood, respectively, and both retain lignin therein; the loaded porous corn cob is corn cob powder that has undergone pore-expanding treatment and has an interface-releasing agent loaded in its pores; the interface-releasing agent includes epoxidized vegetable oil, an aldehyde-containing phenylboronic acid compound, and an epoxy-containing silane coupling agent, wherein the aldehyde-containing phenylboronic acid compound is dispersed in a solid-phase microcrystalline form in a liquid phase composed of the epoxidized vegetable oil and the epoxy-containing silane coupling agent.
[0008] In this invention, the fir fiber and the pine fiber specifically refer to the fibrous powder obtained by mechanically crushing and sieving fir and pine wood. They have not undergone chemical pulping, alkali cooking or bleaching treatment, and therefore retain the lignin content of coniferous wood, which is fundamentally different from pulp fiber in terms of chemical composition.
[0009] The polydopamine layer originates from the mussel-like oxidative self-polymerization of dopamine under weakly alkaline conditions. It can form a firmly attached nanoscale coating layer on the chemically inert, highly crystalline cellulose surface. Its rich catechol groups, quinone groups, and amino groups constitute high-density chemical anchors, providing reaction sites for subsequent epoxy ring-opening grafting and imine condensation, and also initially buffering the stress transfer between the fiber and the matrix with its intrinsic toughness. The lignin-retaining fir and pine fibers perform three functions: the phenolic hydroxyl groups in the phenylpropane structural unit of lignin and their adjacent aliphatic hydroxyl groups provide multidentate coordination sites for borosilicate esterification; the conjugated aromatic ring structure of lignin has ultraviolet absorption and free radical scavenging capabilities, which can protect the polyurethane matrix from photo-oxidation and hydrolysis free radical chain reactions; the flavonoid components in fir and the non-volatile diterpene resin acid components in pine endow the material with certain endogenous antioxidant and antibacterial properties, and the relatively hydrophobic skeleton of lignin inhibits fiber capillary water absorption. The loaded porous corn cob utilizes the well-developed mesopores formed by the hydrothermal expansion of the natural tracheid structure of the corn cob. Like a miniature liquid storage capsule, it physically seals the interfacial release agent in the pores, keeping it inert during the mixing and dispersion stage and releasing it only at specific times and locations during the high-temperature molding stage.
[0010] The aldehyde-containing phenylboronic acid compounds, dispersed in solid-phase microcrystals within the liquid phase, are crucial to ensuring that the interface release agent does not undergo self-crosslinking during storage and mixing. The ring-opening esterification reaction between the boric acid group and the epoxy group requires molecular-level dissolution of boric acid. This compound, a high-melting-point, highly polar crystal, exhibits extremely low solubility below 150°C in a mixture of weakly polar epoxidized vegetable oil and silane. The reaction can only occur at the crystal-liquid interface and is quickly self-inhibited by product coverage. Therefore, the mixture can maintain liquid flowability without gelling for an extended period at the mixing temperature. When the temperature rises above 175°C, the compound's solubility in the liquid phase increases sharply, and it undergoes partial dehydration to form a cyclic boron-oxygen hexacyclic trimer with significantly higher solubility. These two factors together constitute a solubility abrupt change, making the reactive component accessible within a very short time, thus precisely locking the onset of the chemical reaction in the core extrusion reaction zone. The trace amounts of water released in situ during the above dehydration process can be used for the hydrolysis of silane methoxy groups, without the need to introduce additional water into the system.
[0011] The borate group will not be irreversibly fixed by the hydroxyl groups of the corn cob skeleton during loading and storage for three reasons: First, borate esterification requires the hydroxyl groups to meet the geometric configuration of cis-vicinal diols, while the C2 and C3 hydroxyl groups of crystalline cellulose are trans-oriented and locked by intramolecular and intermolecular hydrogen bonds, making them extremely inaccessible; Second, most of the hemicellulose rich in cis-vicinal diol structures in corn cobs has been removed during hydrothermal pore expansion and subsequent hot water washing, significantly reducing the density of its accessible sites; Third, the borate ester bond itself is a dynamic and reversible bond. Even if a small amount is generated on the pore wall, it can be transferred to the more accessible and higher-concentrated target site, the lignin phenolic hydroxyl group, via transesterification when the temperature is raised to the core reaction zone. Therefore, this bond only constitutes a temporary reversible anchoring rather than permanent solidification.
[0012] The three components of the interfacial release agent each perform their specific functions and work synergistically: the long fatty chains of the epoxidized vegetable oil act as chain segment dilution in the cross-linking network, reducing the density of cross-linking points in the interfacial region and imparting hydrophobicity, causing the modulus of the in-situ formed transition layer to decrease gradually from the fiber side to the matrix side, eliminating the modulus step; the phenylboronic acid compound containing aldehyde groups is a bifunctional dynamic cross-linking bridge, whose boric acid groups dehydrate and condense with the phenolic hydroxyl groups and ortho-hydroxyl groups of lignin to form dynamic reversible borate ester bonds, and whose aldehyde groups condense with the amino groups of the polydopamine layer to form dynamic imine bonds, thereby establishing a breakable and regenerable bifunctional dynamic bridge between the rigid skeleton and the lignin nodes; the epoxy-containing The silane coupling agent, on the fiber side, directly undergoes methanol de-condensation at processing temperatures via methoxy groups, cellulose hydroxyl groups, lignin phenolic hydroxyl groups, and polydopamine hydroxyl groups, or condenses after in-situ hydrolysis to silanol groups, achieving covalent anchoring to the fiber surface. On the matrix side, the secondary hydroxyl groups generated by the ring-opening of the epoxy groups and polydopamine amino groups serve as reaction sites, undergoing urethane exchange reactions with the urethane groups of polyurethane above 175°C, and adding to the residual trace isocyanate end groups in the system, thereby forming a covalent bond with the matrix. Simultaneously, hydrogen bonds and chain entanglements between the long-chain structure and the polyurethane soft segments provide additional physical anchoring. The gradient flexible transition layer and dynamic cross-linking network constituted by these three components are the structural basis for resolving the contradiction between low-temperature folding resistance and damp heat peeling in this invention.
[0013] Preferably, by weight, the raw materials for preparing the synthetic leather base layer include 50 to 55 parts of the bio-based polyurethane, 18 to 22 parts of the polydopamine-coated bamboo fiber, 15 to 18 parts of the combined fir and pine fibers, and 8 to 12 parts of the supported porous corn cob; in the supported porous corn cob, the dry weight of the corn cob powder is 6 to 8 parts, and the interface release agent is 2 to 4 parts. When the bio-based polyurethane content is below 50 parts, the continuous melt phase is insufficient, the system viscosity increases sharply, the fiber wetting is poor, and the peel strength and tensile strength decrease significantly; when it is above 55 parts, the proportion of plant fiber system is insufficient, the bio-based carbon content is difficult to reach more than 40%, and the buffer structure is diluted per unit volume. When the polydopamine-coated bamboo fiber content is below 18 parts, the rigid skeleton load-bearing capacity is insufficient, and the tensile modulus and tear resistance decrease; when it is above 22 parts, the high-rigidity fibers overlap and agglomerate, forming stress concentration points and deteriorating melt processability. When the combined amount of fir and pine fibers is less than 15 parts, the density of phenolic hydroxyl nodes is insufficient, the dynamic borate ester network is sparse, and the peel strength retention rate decreases after wet heat aging; when it is more than 18 parts, the total amount of polar hydroxyl groups in the system is excessive, the water absorption channels increase, and excessive coloring is easy to occur during processing. The amount of loaded porous corn cob corresponds to the seepage threshold of the interface release agent buffer network: when it is less than 8 parts, the released interface release agent cannot form a continuous coverage on the surface of the bamboo fiber group, physical discontinuities appear in the buffer layer network, and the improvement in low-temperature folding life is gradual rather than abrupt; when it is more than 12 parts, the corn cob particles agglomerate and weaken the effective load-bearing cross section, and the tensile strength of the base layer drops sharply from more than 15 MPa to less than 8 MPa. The ratio of corn cob dry weight to interface release agent corresponds to the liquid holding capacity of the pore volume after pore expansion; when the amount of interface release agent is less than 2 parts, the release amount is insufficient to completely cover the interface; when it is more than 4 parts, it exceeds the liquid holding capacity of the pores, and leakage occurs during storage and transportation. More preferably, the loaded porous corn cob is 9 to 11 parts, at which point the total amount of release agent matches the total surface area of bamboo fiber better, and the thickness of the gradient flexible transition layer is more uniform; most preferably, the loaded porous corn cob is 10 parts, the buffer network is completely connected without any signs of agglomeration, and the low-temperature folding life reaches the maximum value.
[0014] Preferably, the epoxidized vegetable oil is selected from at least one of epoxidized soybean oil and epoxidized linseed oil, and the number average molecular weight of the epoxidized vegetable oil is 900 to 1000; the aldehyde-containing phenylboronic acid compound is p-formylphenylboronic acid; the epoxy-containing silane coupling agent is γ-glycidoxypropyltrimethoxysilane; and the mass ratio of the three is (4 to 6):(1.5 to 2.5):(2 to 3.5). When the number average molecular weight of the epoxidized vegetable oil is below 900, the flexible chain length is insufficient and there is a risk of plasticizing migration; when it is above 1000, the viscosity is too high, and both pore impregnation and subsequent exudation are hindered. When the proportion of epoxidized vegetable oil is below 4%, the crosslinking point density of the transition layer is too high, the modulus gradient is insufficient, and the low-temperature folding margin is lost; when it is above 6%, the crosslinking density is too low, and the initial peel strength and creep resistance decrease. When the proportion of p-formylphenylboronic acid is less than 1.5%, the dynamic cross-linking nodes are sparse, resulting in insufficient self-healing ability and a decrease in wet heat retention. When it is greater than 2.5%, the solid microcrystals occupy too large a volume within the pores, reducing both the fluidity and permeability of the liquid phase and causing an excessively high proportion of rigid aromatic rings in the transition layer, leading to brittleness. When the proportion of silane coupling agent is less than 2%, the interfacial covalent anchoring is insufficient, resulting in low initial peel strength. When it is greater than 3.5%, the silicon-oxygen network becomes dense, reintroducing the rigid interfacial defects of the prior art. Further preferably, and most preferably, the mass ratio of the three components is 5:2:3. At this point, the ratio of flexible segments, dynamic nodes, and covalent anchors reaches the optimal balance, and both low-temperature flexural strength and wet heat peel strength approach their respective optimal values.
[0015] Preferably, the bamboo fiber has an aspect ratio of 15:1 to 25:1 and a crystallinity greater than 65% as determined by X-ray diffraction; the mass ratio of the fir fiber to the pine fiber is 1:1, both have a particle size of 80 to 120 mesh, and both contain 20% to 35% lignin by mass; the corn cob powder is corn cob powder that has passed through a 200-mesh sieve, and the specific surface area of the corn cob skeleton in the supported porous corn cob is 30 m² / g to 60 m² / g. When the aspect ratio of bamboo fiber is lower than 15:1, the stress transfer length is insufficient, resulting in low reinforcement efficiency; when it is higher than 25:1, the fibers become entangled and break during mixing, leading to deterioration in dispersibility. A crystallinity greater than 65% ensures the modulus and dimensional stability of the skeleton. When fir fiber and pine fiber are mixed in a 1:1 ratio, the antioxidant spectrum of fir flavonoids and pine diterpenoid resin acids is complementary, resulting in the widest free radical capture coverage. When the particle size is coarser than 80 mesh, the inherent defect size of a single fiber increases, becoming a crack source itself; when it is finer than 120 mesh, the specific surface area is too large, exacerbating water absorption and agglomeration. A lignin mass fraction below 20% indicates that the raw material has undergone lignin removal treatment such as alkali cooking or bleaching, resulting in insufficient borate ester site density and simultaneous loss of antioxidant components. The lignin mass fraction of coniferous raw materials is usually no more than 35%. Exceeding this upper limit, the lignin coating layer hinders resin wetting of the cellulose skeleton, and it is prone to excessive color development during high-temperature processing. Passing corn cob powder through a 200-mesh sieve ensures that it does not constitute macroscopic defects in thin base layers, and the pore paths are short, allowing for rapid and complete seepage. When the specific surface area of the corn cob skeleton is below 30 m² / g, it indicates insufficient pore expansion or pore blockage by hydrolysis products, resulting in insufficient liquid holding capacity and release capacity; when it is above 60 m² / g, the skeleton has undergone excessive self-hydrolysis and lacks strength, making it prone to breakage and premature leakage under intensive mixing shearing.
[0016] Preferably, the bio-based polyurethane is a bio-based thermoplastic polyurethane obtained by polymerizing castor oil-based polyols and diisocyanates, wherein the diisocyanate is selected from at least one of 4,4'-dicyclohexylmethane diisocyanate and diphenylmethane diisocyanate; its Shore hardness is 80A to 90A, and its Vicat softening point is 130°C to 150°C. When the Shore hardness is below 80A, the matrix has insufficient room temperature modulus and resilience, and poor abrasion resistance; when it is above 90A, the feel is too hard and the low-temperature brittleness baseline increases. When the Vicat softening point is below 130°C, the product has insufficient heat resistance and the mixing window is too low; when it is above 150°C, the required mixing temperature increases and approaches the dissolution abrupt change temperature of the boric acid component in the interface release agent, posing a risk of premature reaction initiation, which is incompatible with the two-stage temperature control process described later.
[0017] Preferably, the plant fiber-based bio-based synthetic leather further includes a base fabric layer composited with the synthetic leather base layer, the base fabric layer being a non-woven fabric used to improve the tear resistance and dimensional stability of the product; according to ASTM D6866, the bio-based carbon content of the plant fiber-based bio-based synthetic leather is 40% to 50%, meeting the quantitative requirements for renewable components in high-end applications.
[0018] According to another aspect of the present invention, a method for preparing the above-mentioned bio-based synthetic leather based on plant fibers is provided, comprising the following steps: dispersing bamboo fibers in a buffer solution containing dopamine or dopamine hydrochloride for oxidative self-polymerization reaction, and obtaining polydopamine-coated bamboo fibers after separation, washing and drying; pulverizing cedar wood and pine wood respectively, then washing with dilute hydrochloric acid, washing with water and drying to obtain cedar fibers and pine fibers retaining lignin; subjecting corn cob powder to hydrothermal pore-expanding treatment, washing with hot water to remove hydrolysis products and drying, then vacuum impregnating with an impregnation solution under negative pressure, subsequently removing the carrier solvent and drying to obtain supported porous leather. The process involves mixing bio-based polyurethane, polydopamine-coated bamboo fiber, cedar fiber, pine fiber, and loaded porous corn cob at a first temperature. This first temperature is lower than the dissolution temperature of aldehyde-containing phenylboronic acid compounds in the liquid phase, and the interfacial release agent remains within the pores at this temperature. The mixture is then reactively extruded at a second temperature, which is higher than the dissolution temperature. This allows the interfacial release agent to seep out from the pores and undergo in-situ crosslinking with the polydopamine layer, lignin, and bio-based polyurethane. The extruded material is then calendered and cured to obtain bio-based synthetic leather based on plant fibers.
[0019] The core of this method lies in achieving temporal decoupling between dispersion and reaction through two-stage temperature control. In a weakly alkaline buffer solution, the catechol groups of dopamine are oxidized by dissolved oxygen to a quinone structure, which then undergoes Michael addition and Schiff base condensation to gradually crosslink and deposit on the surface of bamboo fibers to form a film. Acid washing with dilute hydrochloric acid removes only ash and metal ions from the fibers without destroying the lignin-carbohydrate linkage structure, fundamentally different from alkaline cooking and bleaching processes, thus preserving the phenolic hydroxyl targets required for dynamic crosslinking from the source.
[0020] Hydrothermal treatment utilizes the autohydrolysis induced by the removal of acetyl groups from hemicellulose to gently expand the pore volume of corn cobs. Hot water washing following hydrothermal treatment is a necessary step in obtaining an effective storage reservoir and cannot be omitted. Autohydrolysis converts hemicellulose into soluble xylooligosaccharides, monosaccharides, and a small amount of furfural products. These substances have extremely high viscosity after cooling. If only filtration is performed without washing, the hydrolysate remaining in the pores will concentrate and precipitate in situ during drying, forming a sticky caramel-like shell that re-blocks the newly expanded mesopores, causing the specific surface area and pore volume to decrease instead of increase, rendering the storage reservoir ineffective. Repeated washing with deionized water at 70°C to 90°C until the total solids content of the filtrate is below 0.05% completely removes the hydrolysate products at a temperature where they still have good water solubility, while further reducing the content of accessible cis-1,5-diols in the skeleton. After washing and drying, the air in the pores is first removed by negative pressure impregnation, and then the impregnation pressure is pushed into the depth of the pores by the pressure difference and capillary action when the normal pressure is restored. Subsequently, the carrier solvent is removed under reduced pressure conditions not higher than 60°C, and the boric acid component is precipitated in situ in the pores as microcrystals and uniformly dispersed in the residual oil phase.
[0021] The interface-releasing agent remains within the pores during the internal mixing stage and seeps out in the extrusion core area. Its physical essence lies in the wetting and extraction process of the liquid within the pores, controlled by viscosity and solubility, rather than relying on mechanical force to squeeze the liquid into or out of the pores. This distinction needs to be made from common intuitive understanding. After pore expansion and washing, the corn cob skeleton is primarily composed of mesopores with pore sizes on the order of 10 nm. Based on capillary pressure estimates, the liquid holding pressure of the interface-releasing agent within these pores is on the order of 10 MPa. In contrast, the shear stress exerted on the material by the internal mixer at speeds of 50 to 70 r / min does not exceed 0.2 MPa, a difference of approximately two orders of magnitude. Furthermore, the corn cob is a lignified, rigid, porous skeleton with a compressive modulus exceeding several hundred MPa, far higher than the stress level in the internal mixing stage. The particles will not be crushed or squeezed out like droplets. Therefore, mechanical shearing does not constitute an effective driving force for the loss of liquid within the pores. The molecular-level dissolution rate truly determines the release timing: at the initial temperature, the bio-based polyurethane has just passed its Vicat softening point, resulting in extremely high melt apparent viscosity, low diffusion coefficient, and low convection renewal rate. The external phase is unable to adequately wet the pores orifices or maintain an effective concentration gradient on the particle surface. Simultaneously, the boric acid component remains undissolved, and even trace amounts of oil phase escaping lack reactivity. Upon entering the core reaction zone, the viscosity of the interfacial release agent decreases by approximately one order of magnitude compared to the initial temperature. The polyurethane melt viscosity also decreases significantly, continuously renewing the material on the particle surface under a high shear field. The pores are adequately wetted, and the liquid phase within the pores is continuously extracted into the melt along the concentration gradient. This extraction process has a characteristic time on the order of tens of seconds at the core reaction zone temperature, but on the order of hours at the initial temperature. Therefore, the residence time window of 45 to 60 seconds becomes the decisive condition for exudation behavior. The role of melt pressure is not to drive exudation, but to inhibit cavitation around the particles, causing the exudated liquid phase to be densely pressed into the interfacial gap between the fiber and the matrix. It is important to emphasize that this invention does not utilize the pressure generated by the vaporization of moisture within the pores. On the contrary, the supported porous corn cob must be dried to a moisture content of less than 0.5% before mixing to prevent moisture from vaporizing during the mixing stage and prematurely carrying the interfacial release agent out of the pores, and to avoid the formation of bubbles in the finished product. The exudated liquid phase is not uniformly dissolved in the matrix, but is preferentially wetted by the highly polar surface of the polydopamine layer. At this point, it is rapidly consumed by the ring-opening grafting of epoxy and amino groups, the iminoization of aldehyde and amino groups, the esterification of boric acid and phenolic hydroxyl groups, and the methanol condensation of silanes. The reaction itself constitutes a continuous concentration trap, thereby achieving localized enrichment and in-situ construction of the transition layer. The curing treatment provides activation energy for the rearrangement of borate ester bonds and the relaxation of polyurethane segments, allowing the dynamic network to reach a thermodynamic equilibrium state.
[0022] Preferably, the buffer solution is a Tris hydrochloric acid buffer solution with a concentration of 8 to 15 mmol / L and a pH of 8 to 9. The temperature for the oxidative self-polymerization reaction is 20°C to 30°C, and the time is 10 to 14 h. Below pH 8, dopamine oxidative self-polymerization is too slow, resulting in insufficient deposition; above pH 9, dopamine self-nucleates in the bulk solution, and polydopamine precipitates as free particles rather than forming a film on the fiber surface. Below 8 mmol / L, the buffer solution concentration is insufficiently stable at pH; above 15 mmol / L, the ionic strength is too high, inhibiting surface deposition. A reaction time shorter than 10 h results in an excessively thin coating layer and insufficient anchor point density; a reaction time longer than 14 h results in an excessively thick and brittle coating layer, and the fibers are prone to agglomeration. Preferably, the mass fraction of the dilute hydrochloric acid is 0.5% to 2%, and the acid washing temperature is 15°C to 35°C. When the mass fraction is below 0.5%, ash and metal ions are not completely removed, and residual metal ions interfere with the selectivity of borosilicate esterification; when it is above 2%, hemicellulose is acidified, lignin is lost, and fiber strength is damaged. Preferably, the hydrothermal pore-expanding treatment temperature is 110℃ to 130℃, and the time is 3 h to 5 h. When the temperature is below 110℃ or the time is less than 3 h, self-hydrolysis is insufficient, pore volume expansion is limited, and liquid holding capacity is insufficient; when the temperature is above 130℃ or the time is longer than 5 h, the corn cob skeleton collapses and a large amount of furfural byproducts are generated, and the liquid holding capacity decreases. Preferably, the hot water washing temperature is 70℃ to 90℃, and washing is performed until the total solid content of the washing filtrate is below 0.05%. When the water temperature is below 70℃, the dissolution and diffusion rate of oligosaccharides is low, the number of washing cycles increases significantly, and the residues deep in the pores are difficult to remove; when the temperature is above 90℃, it approaches boiling, making washing operation inconvenient and possibly causing additional self-hydrolysis. A total solids content in the filtrate higher than 0.05% indicates that soluble substances remain in the pores, which precipitate out and form a shell within the pores after drying. Preferably, the impregnation solution is obtained by dissolving an aldehyde-containing phenylboronic acid compound in anhydrous acetone, and then mixing it with epoxidized vegetable oil and an epoxy-containing silane coupling agent to form a homogeneous solution. Anhydrous acetone, rather than alcohols, is chosen as the carrier solvent because alcohols can undergo alkoxy exchange with the methoxy group of the silane coupling agent, altering its hydrolytic condensation activity. Acetone, on the other hand, has good solubility for the boric acid component, is completely miscible with the other two components, has a low boiling point, and can completely remove the boric acid component at low temperatures. Preferably, the gauge pressure for vacuum impregnation is -0.095 MPa to -0.08 MPa, and the time is 20 min to 40 min. Insufficient vacuum will cause residual gas in the pores to hinder liquid filling, resulting in a low loading rate; degassing will be incomplete if the time is less than 20 min, and there will be no additional gain if the time is longer than 40 min. Preferably, the removal of the carrier solvent is carried out at a temperature not exceeding 60°C and under reduced pressure, resulting in a water content of less than 0.5% after removal. When the solvent removal temperature exceeds 60°C, the solubility of the boric acid component in the liquid phase increases and the moisture content becomes difficult to control, easily forming a localized solidified shell at the pore opening and sealing the pore.
[0023] Preferably, the first temperature is 135°C to 145°C, the mixing time is 8 min to 12 min, and the rotation speed is 50 r / min to 70 r / min. When the first temperature is below 135°C, the material is below the Vicat softening point of the bio-based polyurethane, resulting in no flowability, excessive mixing torque, and poor fiber dispersion. When the temperature is above 145°C, the solubility of the boric acid component in the liquid phase begins to increase, the rate of epoxy ring-opening reaction within the pores is no longer negligible, and the interface release agent risks premature thickening or even gelation. When the time and rotation speed are below the lower limit, dispersion is uneven; when they are above the upper limit, shear heat generation causes localized overheating. Preferably, reactive extrusion is carried out in a twin-screw extruder. The temperatures of each zone from the feeding section to the metering section are 145°C to 155°C, 160°C to 170°C, 175°C to 190°C, and 170°C to 180°C, respectively. The temperature zone from 175°C to 190°C is the core reaction zone, where the residence time of the mixture is 45 s to 60 s, and the melt pressure is 12 MPa to 15 MPa. When the temperature in the core reaction zone is below 175°C, the boric acid component has not passed the dissolution mutation point, and the viscosity of the interfacial release agent is relatively high, resulting in incomplete exudation and discontinuous transition layer coverage. When the temperature is above 190°C, the urethane bonds undergo thermal decomposition accompanied by yellowing, and the high-temperature stability of the urethane bonds also decreases. More preferably, the core reaction zone temperature is 180℃ to 188℃, achieving a better trade-off between complete exudation and the degree of thermal degradation; most preferably, the core reaction zone temperature is 185℃, at which point exudation is complete and matrix degradation is negligible, resulting in optimal overall performance. When the residence time is less than 45 s, both extraction and in-situ crosslinking reactions are incomplete; when it is longer than 60 s, thermal degradation accumulates. When the melt pressure is below 12 MPa, the exudate cannot densely fill the interfacial voids, leaving micropores at the interface; when it is above 15 MPa, die expansion intensifies and fiber orientation stress is frozen within the product. Preferably, the calendering roller temperature is 85℃ to 95℃, and the linear speed is 1.5 m / min to 2.5 m / min, and the calendering is combined with the base fabric layer. When the roller temperature is below 85℃, the base layer and base fabric do not adhere firmly; when it is above 95℃, the surface sticks to the roller and indentations occur; if the linear speed is too fast, the bonding time is insufficient; if it is too slow, excessive accumulation of thermal history occurs. Preferably, the curing temperature is 105°C to 115°C, and the time is 3 h to 5 h. When the temperature or time is below the lower limit, the rearrangement of borate ester bonds and relaxation of chain segments are insufficient, and residual internal stress leads to performance fluctuations; when it is above the upper limit, it constitutes pre-damage due to thermal aging. More preferably, the curing temperature is 110°C and the time is 4 h, so that the dynamic network reaches equilibrium and there is no measurable performance degradation.
[0024] Compared with existing technologies, in a high plant fiber filling system with a bio-based carbon content of 42% to 50%, the synthetic leather of this invention, according to QB / T 2714-2005, exhibits no microcracks or delamination after more than 100,000 bends at -20°C. The optimal implementation scheme reaches 120,000 bends without cracking. In contrast, conventional silane modification techniques with the same filling amount show cracks after only 15,000 to 45,000 bends under the same conditions. This improvement stems from the gradient flexible transition layer formed in situ on the outside of the bamboo fiber polydopamine layer by the exudated interface release agent. Nanoindentation results show that the elastic modulus of this transition layer continuously decreases without abrupt changes from the fiber side to the matrix side within a distance of approximately 240 nm. This allows the strain energy from cyclic bending to be dissipated step by step within the transition layer, eliminating the initiation site for cracks.
[0025] The synthetic leather of this invention has an initial peel strength of not less than 120 N / 3cm, and a peel strength retention rate of not less than 90% after aging at 85℃ and 85%RH for 336 hours. The peel strength of the optimal embodiment only decreases from 128.5 N / 3cm to 119.2 N / 3cm, with a retention rate of 92.8%, while the retention rate of conventional technology under the same aging conditions is only about 43%. Infrared spectroscopy and solid-state nuclear magnetic resonance results show that this result corresponds to the dynamic borate ester bond constructed by p-formylphenylboronic acid and lignin phenolic hydroxyl groups and the dynamic imine bond constructed by p-dopamine amino groups: the hydrolysis and rebonding of the two are in dynamic equilibrium in a humid and hot environment, and the interfacial micro-damage can be closed in situ; at the same time, the hydrophobic long chain of epoxidized vegetable oil and the hydrophobic skeleton of retained lignin block the capillary water absorption channel, and the non-volatile phenolic and resin acid components in coniferous wood capture hydrolytic and oxidative free radicals, cutting off the autocatalytic chain of urethane hydrolysis.
[0026] Furthermore, the synthetic leather of this invention, after being aged under a xenon lamp for 1000 h according to GB / T 16422.2-2022, exhibits a color difference ΔE of no more than 3.0 and shows no whitening, powdering, or cracking. The abrasion mass loss, determined by the Tauber method according to QB / T 2726, is 11.8 mg to 13.1 mg. Without the addition of any antibacterial agents, the material exhibits antibacterial rates of 58% to 66% against Staphylococcus aureus and 47% to 55% against Escherichia coli, respectively. The antifungal grade, determined according to GB / T 24128, is Level 1. It should be objectively noted that volatile monoterpenes such as α-pinene in pine wood are largely lost during the high-temperature processing of intensive mixing and extrusion. The aforementioned antibacterial and antifungal properties originate from non-volatile components that have withstood the processing temperature, namely the phenolic hydroxyl groups and quinone structures of lignin, the quinone groups of polydopamine, and the acid components of pine diterpene resins. Their efficacy is a moderate level of endogenous inhibition and cannot replace dedicated antibacterial agents; they are merely additional properties of the material without the introduction of migratory auxiliaries. The synthetic leather of this invention can be used in upholstered furniture, outdoor furniture, and other fields with stringent requirements for low-temperature performance and weather resistance. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments are briefly described below.
[0028] Figure 1 This is a process flow diagram of the preparation process of plant fiber-based bio-based synthetic leather according to an embodiment of the present invention;
[0029] Figure 2 This is a schematic diagram of the microscopic interface structure of the synthetic leather base layer according to an embodiment of the present invention;
[0030] Figure 3 This is a schematic diagram illustrating the principle of releasing the interface release agent during the thermal processing of a loaded porous corn cob, according to an embodiment of the present invention.
[0031] The components are: 1. Bio-based polyurethane matrix; 2. Bamboo fiber; 3. Polydopamine layer; 4. Gradient flexible transition layer; 5. Fir fiber; 6. Pine fiber; 7. Porous corn cob powder; 8. Base fabric layer; 9. Pore channels; 10. Interface release agent. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the present invention clearer, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the present invention. In the following examples and comparative examples, parts refer to parts by mass, and operations without specified temperatures were performed at room temperature.
[0033] like Figure 1 As shown, the preparation process of this invention sequentially includes polydopamine coating of bamboo fiber, crushing and mild acid washing of fir and pine fibers, hydrothermal pore expansion and hot water washing of corn cob powder, negative pressure vacuum impregnation and low-temperature desolventizing, intensive mixing and pre-dispersion at a first temperature, reactive extrusion at a second temperature, calendering and compounding, and curing treatment. Figure 2 As shown, in the prepared synthetic leather base layer, the surface of bamboo fiber 2 is sequentially coated with polydopamine layer 3 and in-situ formed gradient flexible transition layer 4, and there is no modulus abrupt interface between it and bio-based polyurethane matrix 1; fir fiber 5 and pine fiber 6 are dispersed in the matrix, and their retained lignin and boric acid groups in the interface release agent form dynamic borate ester crosslinking nodes; the porous skeleton remaining after the porous corn cob powder 7 releases the interface release agent continues to serve as toughening and energy absorption sites; the base layer is composited with the base fabric layer 8 below the base layer.
[0034] like Figure 3As shown, within the pore channels 9 of the supported porous corn cob, the interfacial release agent 10 is sealed in a two-phase coexistence form, consisting of a liquid phase, an oil phase, and boric acid microcrystals dispersed therein. During the intensive mixing stage, the pore channels 9 are predominantly mesoporous, and their capillary liquid holding pressure is much higher than the shear stress in the intensive mixing stage. Furthermore, the corn cob is a rigid lignified skeleton and is not crushed to drain the liquid. At the same time, the polyurethane melt has extremely high viscosity and a limited shear rate, making it unable to wet the pore openings and establish an effective concentration gradient. Therefore, the interfacial release agent 10 is basically retained within the pore channels 9. At this time, the boric acid microcrystals have not yet dissolved, and the system does not possess reactive activity. After entering the core reaction zone of extrusion, the boric acid microcrystals cross the dissolution mutation point and completely dissolve into the oil phase and partially dehydrate to form boron-oxygen hexacyclic rings. The viscosity of the interface release agent 10 decreases significantly, the viscosity of the external melt decreases simultaneously, and the material on the particle surface is continuously renewed under a high shear field. The liquid phase in the pores is continuously extracted into the melt along the concentration gradient in a molecular-level dissolution manner, and is densely filled into the interfacial gap between the fiber and the matrix under a melt pressure of 12 MPa to 15 MPa. In the exudated interfacial release agent, the epoxy group of γ-glycidoxypropyltrimethoxysilane undergoes ring-opening grafting with the amino group of the polydopamine layer to generate secondary hydroxyl groups. The methoxy group directly undergoes methanol de-condensation with the hydroxyl groups on the fiber surface or undergoes hydrolysis and condensation after the release of trace amounts of water through boric acid dehydration, achieving covalent anchoring to the fiber side. The generated secondary hydroxyl groups then undergo an exchange reaction with the urethane groups of polyurethane at this temperature, achieving covalent connection to the matrix side. The boric acid group of p-formylphenylboronic acid undergoes dehydration condensation with the phenolic hydroxyl groups of lignin and its side chain ortho-hydroxyl groups to form dynamic borate bonds. The aldehyde group condenses with the amino group of polydopamine to form dynamic imine bonds. The long fatty chain of epoxidized soybean oil dilutes the density of interfacial crosslinking points and imparts hydrophobicity, ultimately forming a flexible transition layer with decreasing modulus gradient and a reversibly reconfigurable dynamic crosslinking network. All of the above reactions proceed spontaneously at the melt processing temperature without the addition of an external catalyst, conforming to the well-known reaction rules of epoxide ring opening, alkoxysilane condensation, borosilicate esterification, Schiff base condensation, and carbamate exchange.
[0035] The raw materials used in the following examples and comparative examples are as follows. Bio-based thermoplastic polyurethane was prepared in-house as follows: 100 parts of vacuum-dehydrated castor oil-based polyester polyol (hydroxyl value approximately 56 mgKOH / g, number-average molecular weight approximately 2000) were bulk polymerized with 35 parts of diphenylmethane diisocyanate and 8 parts of 1,4-butanediol at 120°C and granulated. The isocyanate index was controlled to be 1.0 to 1.05. The resulting product had a Shore hardness of 85A and a Vicat softening point of 140°C. Alternatively, commercially available castor oil-based thermoplastic polyurethane meeting the requirements of a Shore hardness of 80A to 90A and a Vicat softening point of 130°C to 150°C can be used. Dopamine hydrochloride was purchased from Aladdin Reagent (Shanghai) Co., Ltd., with a purity of 98%; p-formylphenylboronic acid (CAS No. 87199-17-5) was purchased from Aladdin Reagent (Shanghai) Co., Ltd., with a purity of 97%, and was a white crystalline powder with a melting point of approximately 245℃; tris(hydroxymethyl)aminomethane was an analytical grade product from Sinopharm Chemical Reagent Co., Ltd., and was prepared into Tris hydrochloric acid buffer by adjusting with hydrochloric acid; anhydrous acetone was an analytical grade product from Sinopharm Chemical Reagent Co., Ltd., and was dried with a 4A molecular sieve before use; epoxidized soybean oil was a commercially available industrial grade product with an epoxy value of not less than 6.0% and a number average molecular weight of approximately 950; γ-glycidoxypropyltrimethoxysilane (trade name KH560) and γ-methacryloyloxypropyltrimethoxysilane (trade name KH570) were purchased from Nanjing Shuguang Chemical Group Co., Ltd., and were industrial grade, and are described by chemical names in the following text; bamboo fiber was commercially available mechanically chopped short fibers from moso bamboo, with a length of 2 mm to 5 mm. mm, aspect ratio 15:1 to 25:1, before use, it was ultrasonically degreased in a 75% ethanol aqueous solution at 500 W for 30 min, rinsed with deionized water and dried at 60℃, and the crystallinity was measured to be 68.2% by X-ray diffraction peak height method; Cunninghamia lanceolata wood chips and Pinus massoniana wood chips are commercially available products, mechanically crushed and sieved to obtain 80-120 mesh fractions, the resulting fibrous powder is the Cunninghamia lanceolata fiber and Pinus massoniana fiber described in this invention; corn cob is agricultural waste, crushed and sieved through a 200 mesh sieve, and its pentosaccharide mass fraction was measured to be 31.5%; the base fabric is commercially available polyester needle-punched nonwoven fabric with a basis weight of 180 g / m²; hydrochloric acid, sodium hydroxide and hydrogen peroxide are all analytical grade products of Sinopharm Chemical Reagent Co., Ltd.
[0036] The performance testing methods are as follows. Bio-based carbon content was determined by accelerator mass spectrometry according to ASTM D6866-22 Method B, and expressed as a percentage of modern carbon to total organic carbon. Lignin content was calculated as the sum of acid-insoluble and acid-soluble lignin. Acid-insoluble lignin was determined according to GB / T 2677.8, and acid-soluble lignin according to GB / T 10337. Samples were pre-treated to remove organic solvent extracts according to GB / T 2677.6. Pentosaccharide content was determined according to GB / T 2677.9. The specific surface area and pore structure of the corn cob skeleton were determined by nitrogen adsorption BET method according to GB / T 19587. Pore size distribution was calculated using the BJH method for self-desorption. Samples were degassed at 120℃ for 6 h before testing. The low-temperature flexural strength was determined according to QB / T 2714-2005. The sample size was 70 mm × 45 mm. The sample was placed in a flexural strength tester equipped with a high and low temperature environment chamber and pretreated at -20℃±2℃ for 4 h before in-situ testing. The bending frequency was (100±5) times / min. The surface and interface were examined with a 10x magnifying glass every 10,000 bends. The appearance after 100,000 bends and the number of bends when the first microcrack appeared were recorded. Peel strength was determined according to GB / T 8949, measuring the peel load between the synthetic leather base layer and the base fabric layer. The sample width was 30 mm, and the peel speed was (100±10) mm / min. The results are expressed as N / 3cm, and the average value of 5 samples in each group was taken. Humid heat aging was conducted in a constant temperature and humidity chamber at 85℃±2℃ and relative humidity (85±3)%. Samples were suspended for 336 h, and after removal, conditioned for 24 h at 23℃±2℃ and relative humidity (50±10)% according to GB / T 2918 before retesting. The peel strength retention rate was the ratio of the peel strength after aging to the initial peel strength. Tensile strength was measured according to GB / T 8949, using longitudinal samples cut according to the sample cross-section, with a tensile speed of 200 mm / min. Abrasion resistance was determined according to QB / T 2726 using the Tabel method, with H-18 grinding wheels, a load of 1000 g per wheel, and 2000 revolutions. Mass loss was measured using an analytical balance with an accuracy of 0.1 mg. Weather resistance was determined according to GB / T 16422.2-2022, method A, cycle 1, with xenon lamp exposure at 0.51 W / (m²·nm) at 340 nm, black standard temperature of 65℃±3℃, alternating cycles of 102 min and 18 min light exposure for a cumulative total of 1000 h. Color difference was measured using a spectrophotometer according to GB / T 7921 and expressed as ΔE*ab in the CIELAB color space. Antibacterial rate was determined according to GB / T 31402-2015 using the film-applied method, with Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 8739 as test strains, and cultured for 24 h. Antifungal performance was determined according to GB / T 24128, and rated based on the area of mold growth after 28 days of incubation. Epoxy value was determined according to GB / T 1677 using the hydrochloric acid-acetone method.The retention rate of the interfacial release agent in corn cob was calculated based on the mass of the extract after Soxhlet extraction with acetone as solvent for 6 h. The boron content in the extract and residue was determined by inductively coupled plasma atomic emission spectrometry. Infrared spectroscopy was performed using attenuated total reflectance mode with a resolution of 4 cm⁻¹ and 32 cumulative acquisitions. Solid boron 11 magic angle rotation NMR spectra were performed with boron trifluoride diethyl ether complex as an external standard at a rotation speed of 12 kHz. The interfacial elastic modulus was determined by nanoindentation using the continuous stiffness method with a Glass indenter. The indenter was scanned across the interfacial line in a direction perpendicular to the bamboo fiber surface with a step size of 50 nm, and the maximum indentation depth was 100 nm. Each point was repeated 10 times and the average value was taken. Dynamic thermomechanical analysis was performed in tensile mode with a frequency of 1 Hz, a heating rate of 3℃ / min, and a temperature range of -80℃ to 100℃.
[0037] Example 1
[0038] One hundred parts of ultrasonically degreased bamboo fiber were dispersed in 2000 parts of Tris hydrochloric acid buffer solution with a concentration of 10 mmol / L and a pH of 8.5. Two parts of dopamine hydrochloride were added, and the mixture was stirred at 25°C for 12 h. After filtration, the mixture was washed three times with deionized water and vacuum dried at 60°C for 8 h to obtain polydopamine-coated bamboo fiber. Fir and pine wood chips were separately pulverized and sieved to obtain 80-120 mesh fractions. These fractions were then soaked and stirred in 1% dilute hydrochloric acid at a bath ratio of 1:20 at 25°C for 30 min, washed with water until neutral, and dried at 60°C to constant weight. The lignin content of the fir fiber was measured to be 30.8%, and that of the pine fiber was 28.3%, consistent with the intrinsic level of coniferous wood, indicating that mild acid washing did not cause delignin removal. Prepare the impregnation solution by mass ratio 5:2:3: Dissolve 2 parts of p-formylphenylboronic acid in 10 parts of anhydrous acetone and stir until completely clear. Then add 5 parts of epoxidized soybean oil and 3 parts of γ-glycidoxypropyltrimethoxysilane in sequence and stir at 25°C for 20 min to obtain a homogeneous impregnation solution. Corn cob powder that had passed through a 200-mesh sieve was ultrasonically washed in deionized water at 500 W for 1 h. It was then transferred to a hydrothermal reactor at a solid-liquid ratio of 1:10 and treated at 120℃ for 4 h. After cooling, it was immediately filtered and repeatedly washed with deionized water at 80℃ at a solid-liquid ratio of 1:15, stirring for 10 min each time before filtration, until the total solid content of the washing filtrate was less than 0.05%. In this example, the washing was carried out 5 times. Subsequently, it was vacuum dried at 60℃ to constant weight. The specific surface area was measured to be 41.6 m² / g, the pore volume was 0.283 cm³ / g, the average BJH pore size was 11.8 nm, and the pentosan mass fraction decreased from 31.5% to 9.8%. The dried porous corncobs were placed in a vacuum impregnation kettle, and the vacuum was drawn to -0.09 MPa and maintained for 30 min. The above impregnation solution was introduced to completely submerge the material. The pressure was restored to normal and impregnation was continued for another 30 min. The surface free liquid was removed by centrifugation, and the material was dried under reduced pressure at 55℃ and -0.09 MPa for 2 h to completely remove anhydrous acetone. The weight was verified so that 3 parts of interface release agent were loaded onto every 7 parts of dry corncobs. The moisture content was measured to be 0.31%, resulting in a loaded porous corncob. Its appearance was a free-flowing dry powder. Under scanning electron microscopy, an oil phase film and needle-like boric acid microcrystals with a particle size of about 0.5 μm to 2 μm were visible on the inner wall of the pores. 52 parts of bio-based thermoplastic polyurethane, 20 parts of polydopamine-coated bamboo fiber, 9 parts of cedar fiber, 9 parts of pine fiber, and 10 parts of loaded porous corncobs were put into an internal mixer and mixed at 140℃ and 60 r / min for 10 min to obtain a mixture.The mixture is fed into a co-rotating twin-screw extruder. The temperatures of each zone from the feeding section to the metering section are set to 150℃, 165℃, 185℃ and 175℃ respectively. The screw speed is 100 r / min. The residence time of the material in the core reaction zone at 185℃ is about 50 s, and the melt pressure is about 13.5 MPa. A sheet with a thickness of about 0.8 mm is extruded through a T-die. The sheet is fed into a calender roll at a roll temperature of 90℃ while still hot and is laminated with polyester needle-punched nonwoven fabric at a linear speed of 2.0 m / min. The laminated sheet is cured at 110℃ for 4 h and then cooled to obtain bio-based synthetic leather based on plant fibers.
[0039] Example 2
[0040] The only difference from Example 1 is the formulation: 55 parts of bio-based thermoplastic polyurethane, 18 parts of polydopamine-coated bamboo fiber, 7.5 parts of cedar fiber, 7.5 parts of pine fiber, and 8 parts of supported porous corn cob, of which 6 parts are dry weight of corn cob and 2 parts are interface release agent.
[0041] Example 3
[0042] The only difference from Example 1 is the formulation: 50 parts of bio-based thermoplastic polyurethane, 22 parts of polydopamine-coated bamboo fiber, 9 parts of cedar fiber, 9 parts of pine fiber, and 12 parts of supported porous corn cob, of which 8 parts are dry weight of corn cob and 4 parts are interface release agent.
[0043] Example 4
[0044] The only difference from Example 1 is that the extrusion temperatures in each zone are 150°C, 165°C, 175°C and 170°C respectively, that is, the core reaction zone temperature is 175°C.
[0045] Example 5
[0046] The only difference from Example 1 is that the extrusion temperatures in each zone are 150°C, 168°C, 190°C and 178°C respectively, that is, the core reaction zone temperature is 190°C.
[0047] Example 6
[0048] The only difference from Example 1 is that the mass ratio of epoxidized soybean oil, p-formylphenylboronic acid and γ-glycidoxypropyltrimethoxysilane in the interface release agent is 4:2.5:3.5.
[0049] Comparative Example 1
[0050] The corn cobs were not subjected to hydrothermal pore expansion, hot water washing, vacuum impregnation and low-temperature desolventizing treatment: 7 parts of ordinary corn cob dry powder that passed through a 200-mesh sieve, 5 parts of epoxidized soybean oil, 2 parts of p-formylphenylboronic acid, and 3 parts of γ-glycidyl etheroxypropyltrimethoxysilane were directly fed into the internal mixer during the internal mixing stage and mixed with the remaining materials. The overall composition of the materials was exactly the same as in Example 1, and the rest of the process was the same as in Example 1.
[0051] Comparative Example 2
[0052] Bamboo fiber was not coated with polydopamine and was used directly after ultrasonic degreasing; fir fiber and pine fiber were boiled in a 5% sodium hydroxide solution at 90°C for 2 hours, then bleached in a 3% hydrogen peroxide solution at 70°C for 1 hour, washed and dried, and the lignin content was measured to be 2.6%; the remaining composition and process were the same as in Example 1.
[0053] Comparative Example 3
[0054] Simulating existing conventional technology: 20 parts of ultrasonically degreased bamboo fiber, 9 parts of alkali-boiled bleached fir fiber, 9 parts of alkali-boiled bleached pine fiber (treatment method the same as Comparative Example 2) were mixed with 10 parts of ordinary corn cob powder. γ-glycidyl etheroxypropyltrimethoxysilane was prepared into a 10% (w / w) ethanol aqueous solution and pre-hydrolyzed for 30 min. 2% (w / w) of the total fiber mass (based on silane) was evenly sprayed onto the surface of the mixed fibers. The spray volume was 20% of the dry weight of the fibers. The material was slightly moist and loose. Subsequently, it was dried at 120℃ for 2 h. The dried fibers and 52 parts of bio-based thermoplastic polyurethane were directly fed into a twin-screw extruder. The extrusion was carried out in one step at a constant temperature of 160℃ and compounded with the same base fabric. No mixing, pre-dispersion, or curing treatment was performed.
[0055] Comparative Example 4
[0056] In the interface release agent, p-formylphenylboronic acid was replaced by an equal mass of γ-methacryloxypropyltrimethoxysilane, i.e., the mass ratio of epoxidized soybean oil, γ-methacryloxypropyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane was 5:2:3. In order to maintain process consistency, anhydrous acetone was still used as the carrier solvent for solution preparation and impregnation and desolventizing were carried out under the same conditions. All other conditions were the same as in Example 1.
[0057] Controlled test on the necessity of hot water washing
[0058] To investigate the effect of the hot water washing step after hydrothermal pore expansion, corn cob slurry from Example 1, which had been hydrothermally treated at 120℃ for 4 h, was cooled, filtered, and then vacuum-dried to constant weight at 60℃ without any washing, serving as a control sample. The specific surface area of this control sample was measured to be only 6.8 m² / g and the pore volume to be 0.052 cm³ / g, both significantly lower than the 41.6 m² / g and 0.283 cm³ / g of the sample after hot water washing, and even only slightly higher than the original corn cob powder without hydrothermal treatment (specific surface area 2.3 m² / g, pore volume 0.021 cm³ / g). Scanning electron microscopy revealed that the pore openings were sealed by a continuous film-like substance, and energy dispersive spectroscopy showed that this film-like substance was a carbohydrate condensation product composed of carbon and oxygen. Vacuum impregnation of this control sample under the same conditions resulted in an interface release agent loading of only 0.42 parts per 7 parts dry corn cob, far lower than the 3 parts in Example 1. The above results indicate that if the soluble oligosaccharides and furfural products generated by hydrothermal autohydrolysis are not washed out at a temperature where the hydrolysis products still have good water solubility, they will precipitate in situ during the drying process and block the newly formed mesopores, causing the storage function to be lost. Therefore, hot water washing is a necessary step in this invention.
[0059] Verification experiment on release timing and reaction process
[0060] To verify the stability of the interfacial release agent during the mixing stage and its release behavior during the extrusion stage, the intermediate material of Example 1 was tracked and measured. The epoxy value of the interfacial release agent loaded in the freshly prepared supported porous corn cob was 3.28%. The supported porous corn cob was kept at 140°C in a sealed container for 10 min. After extraction by Soxhlet extraction, the epoxy value of the soluble residue was 3.16%, and the epoxy value retention rate was 96.4%, indicating that the ring-opening reaction between the boric acid component and the epoxy group was negligible under the mixing temperature and time conditions, and the interfacial release agent maintained liquid phase fluidity without gelation. After the same extraction operation, inductively coupled plasma atomic emission spectrometry (ICP-AES) showed that boron accounted for 96.2% of the total boron in the extract, and only 3.8% remained in the residue, indicating that the boric acid component was not irreversibly fixed by the hydroxyl groups of the corn cob skeleton itself, and the small amount bound was also a reversible surface borate ester. After 90 days of sealed storage at 25℃, the epoxy value retention rate of the supported porous corn cob was 94.8%, and the extracted boron recovery rate was 95.1%, indicating good storage stability. Correspondingly, the corn cob particles were recovered by sieving and extraction from the mixture after 10 min of intensive mixing. The retention rate of the interfacial release agent was measured to be 92.7%, confirming that high-shear intensive mixing did not mechanically extrude the liquid within the pores. Based on the BJH average pore size of 11.8 nm and the surface tension of the interfacial release agent, the capillary liquid holding pressure in the pores was estimated to be on the order of 10 MPa, while the shear stress exerted on the material by the mixer at 60 r / min was less than 0.2 MPa, a difference of approximately two orders of magnitude. After extrusion in the core reaction zone at 185℃, the epoxy value of the extract was measured to decrease to 0.39%, with an epoxy value retention rate of only 11.8%. The retention rate of the interfacial release agent within the corn cob particles decreased to 8.5%, indicating that the interfacial release agent had essentially seeped out and participated in in-situ crosslinking. Solubility measurements further support the above timeline: in a liquid phase prepared from epoxidized soybean oil and γ-glycidoxypropyltrimethoxysilane at a ratio of 5:3, the solubility of p-formylphenylboronic acid is approximately 0.3 g / 100 g at 60 °C, approximately 0.9 g / 100 g at 140 °C, and greater than 8 g / 100 g at 185 °C, accompanied by partial dehydration to form boronoxyhexacyclic rings. The solubility abrupt change point is located in the 170 °C to 180 °C range, which coincides with the lower limit of the set core reaction zone temperature. As a control, if the supported porous corn cob is kept at 160 °C for 10 min, its epoxy value retention rate decreases to 72.5%, verifying the necessity of setting the first upper temperature limit to 145 °C.
[0061] Direct representation of interface structure and dynamic keys
[0062] To directly verify the formation of the gradient flexible transition layer and the dynamic covalent network, rather than relying solely on macroscopic mechanical results for inference, Example 1 and Comparative Example 3 were characterized as follows.
[0063] Infrared spectroscopy showed that the mixture before extrusion curing exhibited a significant absorption at 910 cm⁻¹ attributed to the asymmetric ring stretching of the epoxy group. After extrusion curing, this absorption essentially disappeared, while a new absorption peak appeared at 1638 cm⁻¹, attributed to the imine carbon-nitrogen double bond formed by the condensation of aldehyde and amino groups. An absorption at 1340 cm⁻¹ attributed to the carbon-oxygen-boron bond of the aryl borate ester appeared, and the silicon-oxygen bond absorption at 1080 cm⁻¹ was significantly enhanced. The broad hydroxyl peak near 3400 cm⁻¹ was enhanced due to the formation of secondary hydroxyl groups from the epoxy ring opening and shifted to lower wavenumbers. After the sample was hygrothermally aged at 85℃ and 85%RH for 336 h, the peak area at 1340 cm⁻¹ decreased to 62% of the pre-aging area, but rebounded to 91% after vacuum drying at 50℃ for 24 h, proving that the hydrolysis and rebonding of borate ester bonds under hygrothermal conditions is a reversible process.
[0064] In the magic-angle rotation NMR spectrum of solid boron-11, the supported porous corn cob showed only a single resonance peak at chemical shift 28.4, which is attributed to tricoordinated free arylboronic acid. After extrusion curing, the main peak shifted to chemical shift 30.6, which is attributed to tricoordinated arylboronic esters, and a weak signal of about 7% appeared near chemical shift 8, which is attributed to tetracoordinated borate, indicating that some borate esters formed coordination addition structures with adjacent hydroxyl groups. After wet heat aging, the signal intensity at chemical shift 30.6 decreased while the signal at 28.4 increased. After drying, the two basically returned to the ratio before aging, which is consistent with the infrared results.
[0065] Nanoindentation scanning across the bamboo fiber-matrix interface revealed that the elastic modulus of Example 1 decreased sequentially from 18.6 GPa in the bamboo fiber bulk, through 3.8 GPa in the polydopamine layer, 0.92 GPa inside the transition layer, and 0.21 GPa outside the transition layer, to 0.048 GPa in the matrix. This modulus decrease spanned a spatial scale of approximately 240 nm without any abrupt step changes. In contrast, Comparative Example 3 exhibited a sharp drop from 18.2 GPa to 0.052 GPa over a distance of less than 60 nm, displaying a typical modulus step interface. This result directly corresponds to the significant difference in low-temperature flexural endurance between the two examples.
[0066] In dynamic thermomechanical analysis, Comparative Example 3 showed only a single soft-segment glass transition relaxation peak near -35°C; Example 1, in addition to the corresponding soft-segment relaxation peak at -37°C, also showed a distinct broadened shoulder peak near -12°C. This shoulder peak belongs to an intermediate phase within the interfacial transition layer with low crosslinking density and segment mobility between the fiber and the matrix, providing mechanical spectroscopic evidence for the independent existence of the transition layer. At -20°C, the storage modulus of Example 1 was 1.42 GPa, while that of Comparative Example 3 was 2.35 GPa. The latter is significantly more rigid at low temperatures, consistent with its low-temperature brittle fracture failure mode.
[0067] The performance of the synthetic leathers obtained in each embodiment and comparative example was tested, and the results are shown in Table 1 and Table 2.
[0068] Table 1. Mechanical and durability performance test results of each embodiment and comparative example.
[0069] sample Initial peel strength (N / 3cm) Peel strength after aging (N / 3cm) Peel strength retention rate (%) Appearance after bending 100,000 times at -20℃ Number of bends at which the first microcrack appears (times) Tensile strength (MPa) Bio-based carbon content (%) Example 1 128.5 119.2 92.8 No cracks, no delamination Greater than 120,000 (the test was terminated before the result was achieved) 16.6 47.0 Example 2 131.0 118.5 90.5 No cracks 106000 17.2 42.0 Example 3 120.5 109.8 91.1 No cracks 110000 15.3 50.0 Example 4 124.8 112.5 90.1 No cracks 104000 16.3 46.8 Example 5 123.5 112.0 90.7 No cracks 115000 15.9 46.5 Example 6 130.5 119.1 91.3 No cracks 103000 16.9 47.1 Comparative Example 1 115.0 85.5 74.3 Longitudinal microcracks appeared at the interface 45000 15.6 47.0 Comparative Example 2 108.5 68.2 62.9 Large-area cracking and delamination 60000 14.6 46.3 Comparative Example 3 105.0 45.3 43.1 Severe brittle fracture 15000 13.8 48.0 Comparative Example 4 126.0 98.5 78.2 A small number of interfacial microcracks appeared 92000 16.4 47.1
[0070] Table 2. Surface durability and functional performance test results of each embodiment and comparative example.
[0071] sample Tiber wear mass loss (mg) Color difference ΔE after 1000 h of xenon lamp Surface morphology of xenon lamps after aging Inhibition rate against Staphylococcus aureus (%) Inhibition rate against Escherichia coli (%) Anti-mildew rating Example 1 12.3 2.1 No whitening, powdering, or cracking 62.5 51.8 Level 1 Example 2 13.1 2.4 No whitening, powdering, or cracking 58.7 47.3 Level 1 Example 3 11.8 2.0 No whitening, powdering, or cracking 65.1 54.6 Level 1 Example 4 12.9 2.3 No whitening, powdering, or cracking 61.8 50.9 Level 1 Example 5 12.5 2.6 No whitening, powdering, or cracking 60.4 49.5 Level 1 Example 6 12.0 2.2 No whitening, powdering, or cracking 62.0 51.2 Level 1 Comparative Example 1 16.5 2.8 slight local wrinkles 61.5 50.7 Level 1 Comparative Example 2 18.5 5.8 Obvious yellowing accompanied by powdering and micro-cracking 12.3 8.5 Level 2 Comparative Example 3 21.2 6.7 Whitening, powdering and cracking 10.6 7.2 Level 3 Comparative Example 4 14.8 2.9 No obvious abnormalities 61.9 51.0 Level 1
[0072] The results in Tables 1 and 2 can be uniformly explained from the perspective of interfacial microstructure and functional group synergy, and corroborate the characterization results above. In Examples 1 to 6, at high filling levels with bio-based carbon content ranging from 42.0% to 50.0%, the number of initial cracks at low temperatures all exceeded 100,000, and the wet heat retention rate was not less than 90%, indicating that the gradient flexible transition layer and the dynamic cross-linked network successfully decoupled two previously mutually restrictive performance characteristics. The gradient comparison of corn cob dosage revealed the seepage characteristics of the buffer network: in Example 2, the interfacial release agent released by 8 parts of the loaded porous corn cob was able to maintain continuous coverage, with an initial crack count of 106,000; in Example 1, with 10 parts, the network was completely interconnected and evenly distributed, with an initial crack count exceeding 120,000; in Example 3, with 12 parts, slight agglomeration began to appear, the initial crack count dropped to 110,000, and the tensile strength decreased to 15.3 MPa, approaching the upper limit of seepage. The temperature gradient comparison in the core reaction zone confirms the release sequence based on the abrupt change in solubility and the decrease in viscosity: In Example 4, at 175°C, the boric acid component had just passed the solubility abrupt change point, the viscosity of the interfacial release agent was still relatively high, the extraction and exudation were slightly incomplete, and the initial peel strength and retention rate were the lowest among all examples; In Example 5, at 190°C, exudation was complete, but the matrix showed measurable slight thermal degradation, the initial peel strength decreased slightly, and the color difference increased to 2.6; Example 1 at 185°C achieved both complete exudation and negligible degradation, which is consistent with the jump results of epoxy value retention rate and retention rate in the aforementioned verification test. In Example 6, the increased proportion of rigid crosslinking components increased the initial peel strength to 130.5 N / 3cm, but the steeper gradient of the transition layer modulus reduced the number of first cracks to 103,000, indicating that the mass ratio of 5:2:3 is the balance point of flexible segments, dynamic nodes, and covalent anchors. Regarding damp heat aging, infrared and nuclear magnetic resonance results have shown that the hydrolysis and rebonding of borate ester bonds and imine bonds are in dynamic equilibrium at 85°C and 85%RH, and the interfacial nano-gap generated by damp heat swelling can be closed in situ. The hydrophobic long chains of epoxidized soybean oil and the hydrophobic framework of retained lignin form a dual water-blocking barrier. The phenolic hydroxyl groups of lignin and the acid components of pine diterpene resin continuously capture hydrolytic and photo-oxidative free radicals, severing the amine autocatalytic chain of urethane hydrolysis. It should be noted that lignin itself will generate quinone chromophores under ultraviolet irradiation and has a tendency to yellow. In this invention, lignin is embedded in the polyurethane matrix in the form of fine powder and works synergistically with the polydopamine layer to play a role in ultraviolet absorption and free radical capture. The yellowing of the surface layer is limited to a certain extent. Therefore, the color difference of the example is still significantly lower than that of the comparative example in which the matrix has undergone photo-oxidative whitening.The antibacterial and antifungal results are also consistent with the thermal stability of the components: the antibacterial rate of the examples is at a moderate level rather than a strong bactericidal level, which is consistent with the objective fact that volatile monoterpenes are lost during processing and only non-volatile phenols and resin acids are retained; since the hemicellulose has been reduced from 31.5% to 9.8% by the mass of pentosans during hydrothermal treatment and hot water washing, the lignin content is high and the fiber is embedded in a hydrophobic matrix, the accessibility of polysaccharide components is low, and the antifungal grade of each example is level 1.
[0073] The failure modes of the comparative examples indirectly verified the necessity of each technical feature and their interdependence. In Comparative Example 1, the interface release agent came into direct contact with the melt and was homogeneously diluted during the mixing stage. Although the boric acid component had limited solubility at the mixing temperature, it was dispersed in the bulk along with the matrix in the extrusion stage and could not be enriched into a layer at the fiber interface. The modulus step between the bamboo fiber and the matrix still existed, and the number of first cracks dropped sharply to 45,000. At the same time, the boric acid ester nodes were diluted in the bulk, with a retention rate of only 74.3%. This proves that the spatial isolation and localized release function provided by the corn cob reservoir, rather than the release agent itself, is the prerequisite for the formation of the gradient transition layer. In Comparative Example 2, the lack of polydopamine anchors resulted in insufficient coupling of silanes to the limited accessible hydroxyl groups on the highly crystalline cellulose surface, causing the initial peel strength to drop to 108.5 N / 3 cm. Furthermore, after lignin was removed by alkali boiling and bleaching, boric acid lost its phenolic hydroxyl target, allowing moisture to rapidly penetrate along the exposed hydrophilic capillary channels, triggering hydrolysis and autocatalysis. The retention rate plummeted to 62.9%, and both UV shielding and endogenous antibacterial functions collapsed simultaneously. The color difference reached 5.8, and the antibacterial rate decreased to 12.3% and 8.5%, respectively, with the antifungal grade dropping to level 2. This demonstrates that retaining lignin simultaneously fulfills multiple roles as a crosslinking site, photoprotection, and antibacterial functional carrier. In Comparative Example 3, the conventional silane route formed a dense, rigid silica layer with residual hydrophilic silanol groups on the fiber surface. Nanoindentation showed a sudden drop in interfacial modulus within 60 nm. Thermal expansion mismatch at low temperatures led to brittle fracture after 15,000 cycles, and interfacial hydrolysis under humid heat reduced the retention rate to only 43.1%, fully replicating the coupling contradictions described in the background art. In Comparative Example 4, after replacing p-formylphenylboronic acid with γ-methacryloxypropyltrimethoxysilane by mass, static covalent coupling still achieved an initial exfoliation strength of 126.0 N / 3 cm. However, the interface lost its dynamic re-closing ability, and the retention rate decreased from 92.8% to 78.2%. Furthermore, the energy dissipation contribution of the dynamic bonds disappeared, reducing the number of initial cracks to 92,000. Quantitative exfoliation revealed the independent contributions of dynamic borate esters and imine chemistry to hydrothermal stability and low-temperature toughness. In summary, the technical effect of this invention stems from the interfacial microstructure reconstructed by the heterogeneous specialization of the four plant-derived components and the two-stage temperature-controlled processing. Each feature is interdependent and indispensable, rather than a simple sum of the formulation components.
[0074] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A bio-based synthetic leather based on plant fibers, characterized in that, Includes a synthetic leather base layer, wherein the raw materials for preparing the synthetic leather base layer include bio-based polyurethane and plant fiber systems; The plant fiber system includes polydopamine-coated bamboo fiber, fir fiber, pine fiber, and loaded porous corn cob. The polydopamine-coated bamboo fiber is bamboo fiber with a polydopamine layer coated on its surface. The fir fiber and the pine fiber are fibrous powders obtained by mechanically crushing fir and pine wood, and both retain lignin. The loaded porous corn cob is corn cob powder that has undergone pore-expanding treatment and has an interface-releasing agent loaded in the pores. The interface release agent includes epoxidized vegetable oil, aldehyde-containing phenylboronic acid compounds, and epoxy-containing silane coupling agents, wherein the aldehyde-containing phenylboronic acid compounds are dispersed in solid-phase microcrystal form in a liquid phase composed of the epoxidized vegetable oil and the epoxy-containing silane coupling agent.
2. The bio-based synthetic leather based on plant fibers according to claim 1, characterized in that, By weight, the raw materials for preparing the synthetic leather base layer include 50 to 55 parts of the bio-based polyurethane, 18 to 22 parts of the polydopamine-coated bamboo fiber, 15 to 18 parts of the combined fir and pine fibers, and 8 to 12 parts of the supported porous corn cob; in the supported porous corn cob, the dry weight of the corn cob powder is 6 to 8 parts, and the interface release agent is 2 to 4 parts.
3. The plant fiber-based bio-based synthetic leather according to claim 1 or 2, characterized in that, The epoxidized vegetable oil is selected from at least one of epoxidized soybean oil and epoxidized linseed oil, and the number-average molecular weight of the epoxidized vegetable oil is 900 to 1000. The phenylboronic acid compound containing an aldehyde group is p-formylphenylboronic acid; The epoxy-containing silane coupling agent is γ-glycidoxypropyltrimethoxysilane; The mass ratio of the epoxidized vegetable oil, the aldehyde-containing phenylboronic acid compound, and the epoxy-containing silane coupling agent is (4 to 6):(1.5 to 2.5):(2 to 3.5).
4. The plant fiber-based bio-based synthetic leather according to claim 1 or 2, characterized in that, The bamboo fiber has an aspect ratio of 15:1 to 25:1, and the crystallinity of the bamboo fiber, as determined by X-ray diffraction, is greater than 65%; the mass ratio of the fir fiber to the pine fiber is 1:1, both have a particle size of 80 mesh to 120 mesh, and both contain 20% to 35% lignin by mass; the corn cob powder is corn cob powder that has passed through a 200-mesh sieve, and the specific surface area of the corn cob skeleton in the supported porous corn cob is 30 m² / g to 60 m² / g.
5. The plant fiber-based bio-based synthetic leather according to claim 1 or 2, characterized in that, The bio-based polyurethane is a bio-based thermoplastic polyurethane obtained by polymerizing castor oil-based polyol with diisocyanate, wherein the diisocyanate is selected from at least one of 4,4'-dicyclohexylmethane diisocyanate and diphenylmethane diisocyanate; the bio-based polyurethane has a Shore hardness of 80A to 90A and a Vicat softening point of 130°C to 150°C.
6. The plant fiber-based bio-based synthetic leather according to claim 1 or 2, characterized in that, The plant fiber-based bio-based synthetic leather also includes a base fabric layer composited with the synthetic leather base layer, the base fabric layer being a non-woven fabric; the bio-based carbon content of the plant fiber-based bio-based synthetic leather is 40% to 50% as determined by ASTM D6866.
7. A method for preparing plant fiber-based bio-based synthetic leather as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Bamboo fibers were dispersed in a buffer solution containing dopamine or dopamine hydrochloride and subjected to an oxidative self-polymerization reaction. After separation, washing and drying, the polydopamine-coated bamboo fibers were obtained. After being crushed into pine and fir wood respectively, the pine and fir fibers were subjected to acid washing with dilute hydrochloric acid, water washing and drying to obtain pine and fir fibers that retain lignin. After the corn cob powder is subjected to hydrothermal pore-expanding treatment, it is washed with hot water to remove hydrolysis products and dried. Then, it is vacuum impregnated with an impregnation solution under negative pressure. Subsequently, the carrier solvent in the impregnation solution is removed and dried to obtain the supported porous corn cob. The bio-based polyurethane, the polydopamine-coated bamboo fiber, the cedar fiber, the pine fiber, and the supported porous corn cob are intensively mixed at a first temperature to obtain a mixture. The first temperature is lower than the dissolution temperature of the aldehyde-containing phenylboronic acid compound in the liquid phase, and the interface release agent is retained in the pores of the supported porous corn cob at the first temperature. The mixture is reactively extruded at a second temperature, which is higher than the dissolution mutation temperature, so that the interface release agent seeps out from the pores of the supported porous corn cob and undergoes an in-situ crosslinking reaction with the polydopamine layer, the lignin, and the bio-based polyurethane. The extruded material is calendered and cured to obtain the plant fiber-based bio-based synthetic leather.
8. The preparation method according to claim 7, characterized in that, The buffer solution is a Tris hydrochloric acid buffer solution with a concentration of 8 mmol / L to 15 mmol / L and a pH of 8 to 9. The temperature of the oxidative self-polymerization reaction is 20°C to 30°C, and the time is 10 h to 14 h. The mass fraction of the dilute hydrochloric acid is 0.5% to 2%, and the pickling temperature is 15°C to 35°C. The hydrothermal pore-expanding treatment is performed at a temperature of 110°C to 130°C for 3 to 5 hours. The hot water temperature for washing is 70°C to 90°C, and washing continues until the total solids content of the washing filtrate is less than 0.05%. The impregnation solution is obtained by dissolving the aldehyde-containing phenylboronic acid compound in anhydrous acetone, and then mixing it with the epoxidized vegetable oil and the epoxy-containing silane coupling agent to form a homogeneous solution; The vacuum impregnation was performed at a gauge pressure of -0.095 MPa to -0.08 MPa for a time of 20 min to 40 min. The removal of the carrier solvent is carried out at a temperature not exceeding 60°C and under reduced pressure, and the moisture content of the supported porous corn cob after removal is less than 0.5%.
9. The preparation method according to claim 7, characterized in that, The first temperature is 135°C to 145°C, the mixing time is 8 min to 12 min, and the rotation speed is 50 r / min to 70 r / min; the reactive extrusion is carried out in a twin-screw extruder, and the temperatures of each temperature zone from the feeding section to the metering section of the twin-screw extruder are 145°C to 155°C, 160°C to 170°C, 175°C to 190°C, and 170°C to 180°C, respectively. The temperature zone with a temperature of 175°C to 190°C is the core reaction zone, and the second temperature is the temperature of the core reaction zone; the residence time of the mixture in the core reaction zone is 45 s to 60 s, and the melt pressure is 12 MPa to 15 MPa.
10. The preparation method according to claim 7, characterized in that, The calendering roll temperature is 85°C to 95°C, and the linear speed is 1.5 m / min to 2.5 m / min. During calendering, the extruded material is combined with the base fabric layer. The curing treatment temperature is 105°C to 115°C, and the time is 3 h to 5 h.
